Effectiveness of the implementation of service retribution collection at the Parungkuda semi-modern market, Sukabumi Regency - Ratu Tasya Istanda; M. Rijal Amirullah; Rizki Hegia Sampurna (Journal of Community Service and Empowerment, 2024)
Parungkuda Semi Modern Market is one of the government facilities used by traders. There are 600 traders who use the market facilities, and are obliged to pay market levies. The aim of this research is to prove the effectiveness of the implementation of collecting market service levies in the Parungkuda semi-modern market, Sukabumi Regency. This research uses descriptive qualitative methods. Parungkuda Semi-Modern Market is a market that is used as the unit of analysis and researchers determine key informants, including the Parungkuda Market UPT coordinator, assistant treasurer, collectors and market traders. The data collection techniques used in this research are through participant observation, interviews and documentation. To test the validation of the information data that has been collected, researchers use a credibility test through a triangulation process. The results of this research indicate that the implementation of service levy collection at the Parungkuda Semi-Modern Market, Sukabumi Regency, has a high level of effectiveness. Several factors that support this effectiveness include a good management system, active participation from traders and market visitors, as well as strict supervision of the levy collection process. Thus, it can be concluded that the implementation of service levy collection in the market is running well and effectively.